Should the Principles of Digital Development be Agile? - ICTworks (2016)
Recently, Abt Associates endorsed the “Principles of Digital Developme nt.” These nine principles have been widely adopted by international d evelopment funders and practitioners to absorb and disseminate technol ogy best practices in the field of international development. More tha n 50 organizations ranging from various offices in the United Nations and the U.S. Agency for International Development (USAID) down to nich e technology providers have endorsed the principles. The principles ar e aimed at moving the field away from a disconnected series of technol ogy pilots, each of which are largely ad hoc and duplicate many of the same lessons, and toward scalability and sustainability. Ann Mei Chan g, the Executive Director of the U.S. Global Development Lab at USAID in her foreword to the recent report “From Principle to Practice: Impl ementing the Principles for Digital Development”, characterized the pr oblem that these principles are trying to address as follows: “Pilots have failed to move